2019
DOI: 10.1186/s12885-019-6274-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary solid lung cancerous nodules with different sizes: computed tomography features and their variations

Abstract: Background:The computed tomography (CT) features of small solid lung cancers and their changing regularity as they grow have not been well studied. The purpose of this study was to analyze the CT features of solid lung cancerous nodules (SLCNs) with different sizes and their variations. Methods: Between February 2013 and April 2018, a consecutive cohort of 224 patients (225 nodules) with confirmed primary SLCNs was enrolled. The nodules were divided into four groups based on tumor diameter (A: diameter ≤ 1.0 c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…There were statistically significant differences in nodule size between the two groups, and Chu et al. ( 30 ) found that larger pulmonary nodules (diameter >1 cm) had more malignant CT features compared with smaller nodules (diameter <1 cm) in patients with solid lung cancerous nodules. Patients with LTB tended to have mediastinal lymphadenectasis compared to LAC patients in our study, but Zhu et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There were statistically significant differences in nodule size between the two groups, and Chu et al. ( 30 ) found that larger pulmonary nodules (diameter >1 cm) had more malignant CT features compared with smaller nodules (diameter <1 cm) in patients with solid lung cancerous nodules. Patients with LTB tended to have mediastinal lymphadenectasis compared to LAC patients in our study, but Zhu et al.…”
Section: Discussionmentioning
confidence: 98%
“…Vacuole sign is often seen in malignant nodules, which is an important sign of early lung cancer, but also occasionally seen in benign nodules (28,29). There were statistically significant differences in nodule size between the two groups, and Chu et al (30) found that larger pulmonary nodules (diameter >1 cm) had more malignant CT features compared with smaller nodules (diameter <1 cm) in patients with solid lung cancerous nodules. Patients with LTB tended to have mediastinal lymphadenectasis compared to LAC patients in our study, but Zhu et al (31) found that malignant diseases were mostly in the diseases with mediastinal lymphadenectasis, and the benign diseases were mainly granuloma in a cohort study with 846 patients who underwent endobronchial ultrasound-guided transbronchial needle aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…approximately 35% (range: 21-58%) (9-12). Chu et al reported that 95% (214/225) of solid cancerous nodule had a regular shape (30). Also, Zerhouni et al recorded that 25% of benign nodules showed irregular margins with lobulation or spiculation, and only 18% of these lesions were correctly assessed on CT (9).…”
Section: Discussionmentioning
confidence: 99%
“… 19 In lung cancers, heterogeneous lesions would become homogeneous as growing due to tumor cell proliferation, but this change would not happen in inflammatory nodules. 19 , 24–26 Therefore, follow-up for monitoring density change is useful for differentiating heterogeneous nodules.…”
Section: Discussionmentioning
confidence: 99%